2020
DOI: 10.3390/coatings10040345
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure Observation and Nanoindentation Size Effect Characterization for Micron-/Nano-Grain TBCs

Abstract: Microstructure observation and mechanical properties characterization for micron-/nano-grain thermal barrier coatings were investigated in this article. Scanning electron microscope images demonstrated that both micron-grain coating and nano-grain coating had micrometer-sized columnar grain structures; while the nano-grain coating had the initial nanostructures of the agglomerated powders reserved by the unmelted particles. The mechanical properties (hardness and modulus) of micron-/nano-grain coatings were ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Nanoindentation is widely used for determining mechanical properties of materials by analyzing the load-displacement curve [1,2], while atomic force microscopy (AFM) is an essential tool for analyzing the deformation of material during indentation [3,4]. In order to perform experiments on a new material, an experimentalist relies on their experience or refers to the literature on tests performed on similar systems, and accordingly designs their approach regarding applied load and holding time for similar systems [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Nanoindentation is widely used for determining mechanical properties of materials by analyzing the load-displacement curve [1,2], while atomic force microscopy (AFM) is an essential tool for analyzing the deformation of material during indentation [3,4]. In order to perform experiments on a new material, an experimentalist relies on their experience or refers to the literature on tests performed on similar systems, and accordingly designs their approach regarding applied load and holding time for similar systems [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In-depth studies of the release of Ni and Cr ions into aqueous solutions have shown very good barrier properties of these coatings, therefore they can significantly contribute to reducing potential cytotoxicity and improving the biocompatibility of prosthetic alloys. The last work on the barrier ceramic coatings was that of Liu et al [7], about the microstructure and mechanical properties of 8% yttria-stabilized zirconia (8YSZ) thermal barrier coatings deposited on Ni-based superalloy (GH3128) by plasma spraying. The authors analyzed the effect of the parameterdependent plasma spraying deposition process on the microstructure of the coatings and their micromechanical properties.…”
mentioning
confidence: 99%